Young Mandarin learners use function words to distinguish between nouns and verbs. Issue 5 (17th December 2019) - Ma, Weiyi; Zhou, Peng; Golinkoff, Roberta M.
Abstract: Mandarin requires neither determiners nor morphological inflections, which casts doubt on Mandarin‐speaking children's ability to use function words as a syntactic bootstrapping tool to identify the form class of a new word. This study examined 3‐ and 5‐year‐old Mandarin learners' ability to use function words to interpret new words as either nouns or verbs in the absence of the requirement for determiners and inflections in the ambient language. In Experiment 1, 3‐, and 5‐year‐old Mandarin‐speaking children were exposed to eight novel words embedded in sentence frames differing only in the form class markers used. The 5‐year‐olds interpreted the novel words as either nouns or verbs depending on the form class markers they heard, while the 3‐year‐olds learned only the nouns. Experiment 2 confirmed that the 5‐year‐olds understood the function of the verb‐marker. Thus, Mandarin‐speaking children can use function words to distinguish nouns versus verbs, and this ability appears between three and five years of age. Abstract : Three‐ and five‐year‐old Mandarin‐learning children were exposed to novel words embedded in sentence frames differing only in the form class markers used. The 5‐year‐olds interpreted the novel words as either nouns or verbs depending on the form class markers they heard, while the 3‐year‐olds learned only the nouns. Mandarin‐learning children use function words to interpret new words as nouns versus verbs. This ability appears in Mandarin learners between 3 and 5 years of age.